Accounting Information and Psychological Factors in Capital Market : Do these Affect the Investors’ Decisions to Invest? - Latief, Nur Fitry; Niu, Fitria Ayu Lestari (Jurnal Reviu Akuntansi dan Keuangan)
This study aims to determine the effect of accounting information and psychological factors on investor decision to invest in the capital market. The data come from questionnaire with a Likert scale measurement tool. The object was the investors of PT MNC Sekuritas Manado who were respondents as many as 119 investors. Data analysis uses multiple linear regression analysis with SPSS Version 25. The results find that partially and simultaneous the accounting information and psychological factor had a positive and significant effect on investor decision. This shows that the increasing accounting information and psychological factors available will increasingly influence the decision making of investors. But from the partial t-test results, it was found that the accounting information had more influence than the psychological factor, it means that investors tend to be rational in making their investment decisions by using accounting information as consideration for their decision making. This study provides empirical evidence regarding the influence of accounting information and psychological factors on investors' decisions to invest in the capital market and give contributions to academics and researchers by supporting the theory and results of previous research on the same topic.